HUBUNGAN ANTARA PENGETAHUAN KELUARGA TENTANG PENDIDIKAN SEKS DENGAN PERILAKU KELUARGA DALAM PEMBERIAN PENDIDIKAN SEKS PADA REMAJA - Agustina, Emi; Hapsari, Risma Widya (Akademi Keperawatan Pamenang, 2012)
Sex education is an information regarding human sexual problems clearly and correctly, including the process of fertilization pregnancy until birth, sexual behavior and health aspects, psychological and social problems associated with proper sex education, the prevailing norms in society. The purpose of this research is to know is there any correlation between family knowledge about sex education with family behavior in the provision of sex education on teenagers. In this study using cross sectional study design. Population of more than 30 people and taken 30 samples in Orchard Village Templek Gadungan. The experiment was conducted at 10 to 15 May 2010 with a total sampling techniques. Collecting data for the independent and dependent variables are family knowledge about sex education with family behavior in the provision of sex education in adolescents by using questionnaires and then analyzed using a descriptive cross-tabulations. The results obtained by respondents with better knowledge behavioral fairly good knowledge of the behavior as much as 6.7% to 6.7%, enough, enough knowledge of the behavior of 36.7% with 13.3% and less adequate 23.3%, and 56 lack of knowledge, 7% to 56.7% less behavior. And proved it shows that there is correlation between knowledge about sex education, family with family behavior in the provision of sex education on teenagers. We can conclude that a persons actions must be based on knowledge of the role of nurses as educators are expected to provide sex education to families and young adolescents.